PERFORMANCE MANAGEMENT SYSTEM AND EMPLOYEES’ PERFORMANCE IN FEDERAL MEDICAL CENTRE, KEFFI, NASARAWA STATE - Bello, Adewale James; Kassah, Virginia; Shittu, Olabisi (African Journal of Social and Behavioural Sciences, 2025)
Organisations often appraise the performance of their staff so as to know their current and future skills. The effectiveness of the implementation of performance management practices depends on a variety of factors that are interrelated to the success of the implementation in organisations. This study examines the effect of performance management systems on employees’ performance in Federal Medical Centre, Keffi, Nasarawa State. The study adopted a descriptive research design, and the population was comprised of 3,700 employees of Federal Medical Centre, Keffi, Nasarawa State, of which an estimated sample size of 361 was drawn using Taro Yamane’s (1967) formula. Data collected was analysed using descriptive statistics, correlation, and multiple linear regression. The study found that performance planning significantly improves employees’ performance in Federal Medical Centre, Keffi, while reward does not significantly improve employees’ performance in Federal Medical Centre, Keffi. The study concluded that the performance management system has a positive and significant effect on employees’ performance in Federal Medical Centre, Keffi, Nasarawa State. The study recommends that the management of Federal Medical Centre, Keffi, Nasarawa State should prioritize a comprehensive reward scheme that incorporates both financial and non-financial programmes in the appropriate proportion through employees’ involvement in such policy design.